2013
DOI: 10.1080/1062936x.2013.766634
|View full text |Cite
|
Sign up to set email alerts
|

On the rational formulation of alternative fuels: melting point and net heat of combustion predictions for fuel compounds using machine learning methods

Abstract: We report the development of predictive models for two fuel specifications: melting points (T(m)) and net heat of combustion (Δ(c)H). Compounds inside the scope of these models are those likely to be found in alternative fuels, i.e. hydrocarbons, alcohols and esters. Experimental T(m) and Δ(c)H values for these types of molecules have been gathered to generate a unique database. Various quantitative structure-property relationship (QSPR) approaches have been used to build models, ranging from methods leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…At the same time, advances in applying quantitative structure property relationship (QSPR) and quantitative structure activity relationship (QSAR) techniques have led to improved predictions of cetane number [143][144][145], flashpoint [144], density and viscosity [146], melting point [147], heat of combustion [147], and laminar burning velocities of biofuels [148]. Recently, Saldana et al [149] have suggested QSPR based methods for formulating alternative fuels for specific applications.…”
Section: Advances In Chemical Analysis Methodsmentioning
confidence: 99%
“…At the same time, advances in applying quantitative structure property relationship (QSPR) and quantitative structure activity relationship (QSAR) techniques have led to improved predictions of cetane number [143][144][145], flashpoint [144], density and viscosity [146], melting point [147], heat of combustion [147], and laminar burning velocities of biofuels [148]. Recently, Saldana et al [149] have suggested QSPR based methods for formulating alternative fuels for specific applications.…”
Section: Advances In Chemical Analysis Methodsmentioning
confidence: 99%
“…The data sets used in the literature to model the DH o c of pure compounds (Cardozo, 1986;Gharagheizi, 2008;Pan et al, 2011;Cao and Wang, 2013;Seaton and Harrison, 1990;Hshieh, 1999;Hshieh et al, 2003;Diallo et al, 2012;Wang and Li, 2000;Van Krevelen, 1990;National Technical Information Service (NTIS), 2001;Gharagheizi et al, 2011;Cao et al, 2009;Saldana et al, 2013;Albahri, 2013a) are so different that these models cannot be compared to one another. However, Table 2 shows that our proposed SGC-ANN model gives good results compared to the other models used to calculate DH o c .…”
Section: Sgc-ann Modelmentioning
confidence: 99%
“…Saldana et al (Saldana et al, 2013) combined several methods to create a consensus model for predicting the DH o c of 1624 hydrocarbon-based compounds and 1143 oxygenates (alcohols and esters) using QSPR. Various approaches were investigated from linear modeling: Genetic Function Approximation (GFA) and Partial Least Squares (PLS) to nonlinear models, such as FeedForward Artificial Neural Network (FFANN), General Regression Neural Networks (GRNN), Support Vector Mechanics (SVM), and Graph Machines (GM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A different model, the Graph Machines, 16 was developed for QSAR 17 and was recently used for predicting fuel combustion properties. 18 This article presents a combination of the fundamental graph processing connectionist model, RAAM, with the Sensitivity Based Linear Learning Method, which resulted in a model that can be efficiently trained in a very few iterations…”
Section: Introductionmentioning
confidence: 99%